Ergonomics Assessment Of Tin Snips - syed mohamed, muhammad syafiq (2011)
Tin snips are widely used for sheet metal cutting, mesh wire screening, leather, asphalt roof shingles and many more. Depending on the design of the tin snips, the design may contribute to various ergonomic risk factors, such as excessive forces and awkward postures of the upper limb. An ergonomics assessment was conducted for 3 different tin snips (XI, X2 and X3).Hand tool comfort assessment questionnaire designed by Kuijt - Evers et a1 f2004) was utilized in this study. Eighty participants rated the tin snips. Results indicated that tin snip x3 (55.94%) gave the best score for ergonomics compared to XI (51.48%) and x2 (54,06%).Participants were able to estimate certain ergonomic features such as good posture, absence of peak pressures on the palm and good friction force during the evaluation.